2022
DOI: 10.11591/ijece.v12i6.pp6585-6593
|View full text |Cite
|
Sign up to set email alerts
|

An automated essay evaluation system using natural language processing and sentiment analysi

Abstract: <span lang="EN-US">An automated essay evaluation system is a machine-based approach leveraging long short-term memory (LSTM) model to award grades to essays written in English language. <a name="_Hlk108785338"></a>natural language processing (NLP) is used to extract feature representations from the essays. The LSTM network learns from the extracted features and generates parameters for testing and validation. The main objectives of the research include proposing and training an LSTM model usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The primary goals of the study reported in [42] are the proposal and training of a long-short-term memory (LSTM) model on a collection of hand evaluated essays with scores. The purpose of sentiment analysis is to establish whether an article is positive, negative, or neutral.…”
Section: Related Workmentioning
confidence: 99%
“…The primary goals of the study reported in [42] are the proposal and training of a long-short-term memory (LSTM) model on a collection of hand evaluated essays with scores. The purpose of sentiment analysis is to establish whether an article is positive, negative, or neutral.…”
Section: Related Workmentioning
confidence: 99%
“…CNN is an example of a feedforward network, in which information only flows in a single direction, from input to output [28], [29]. Even though there are several CNN architectures, most CNNs have convolutional and pooling layers.…”
Section: Introductionmentioning
confidence: 99%
“…The ontology of ATP modern methods includes both classical ATP methods and methods using machine learning. The papers [19]- [21] existing ontologies containing ATP methods were analyzed. At the moment, there is an ontology of machine learning [22], [23] which contains a small set of ATP methods based on machine learning.…”
Section: Introductionmentioning
confidence: 99%